Cyclic Electrical Energy Harvesting Using Mechanical Confinement in Ferroelectric Ceramics. Issue 4 (19th December 2014) - Vats, Gaurav; Patel, Satyanarayan; Chauhan, Aditya; Vaish, Rahul
<x xml:space="preserve">Abstract</x> Present study introduces a novel energy conversion cycle for giant electro‐mechanical energy conversion using ferroelectric materials. The proposed cycle is used to perform indirect measurements for harnessable energy densities of two well‐known configurations ((0.5PbZrO3‐0.5Pb(Ni1/3Nb2/3)O3: (PZ‐PNN) and 0.9Pb(Zr1/2Ti1/2)O3‐0.1Pb(Zn1/3Nb2/3)O3: (0.9PZT‐0.1PZN)). PZ‐PNN is depicted to illustrate an energy density of 70 kJ/m3 under the conditions of 0–106 MPa applied stress and 1–15 kV/cm electric field. On the other hand, a maximum energy density of 50 kJ/m3 is obtained for 0.9PZT‐0.1PZN under ambient conditions of 0–173 MPa compressive stress and 1 to 18 kV/cm electric field.